Secondary school teachers’ perspectives towards the implementation of CEFR-Aligned English Curriculum / Shahazwan Mat Yusoff, Mazlen Arepin and Anwar Farhan Mohd Marzaini - Mat Yusoff, Shahazwan; Arepin, Mazlen; Mohd Marzaini, Anwar Farhan (Universiti Teknologi MARA, Kedah, 2022)
In strengthening English language proficiency among Malaysian students, Ministry of Education (MOE) has integrated the Common European Reference Framework (CEFR) into the education system and developed action plans for the systematic reform of English education. CEFR does not only describe on the aspects of English that are commonly learned at each level, but also tells teachers, curriculum developers, course authors and test writers what is appropriate to learn at each level. Hence, teachers must have sufficient knowledge on how to implement CEFR into their teaching accordingly and this is due to the fact that the effectiveness of this educational reform is heavily reliant on them. The methodological framework used in this study is phenomenological study. It is intended to grasp the perspectives on CEFR-Aligned curriculum among English language teachers. Interviews were conducted on 10 English language teachers teaching in five different schools in Petaling Utama district. Purposive sampling was used as the sample method. Data gathered were analysed by using thematic analysis. The result indicates that there are two major themes that emerged from thematic analysis which are autonomous learning and pedagogical approach. Teachers agreed that awareness of students’ level of proficiency is central to CEFR-aligned curriculum not merely due to the fact that it helps teachers to design lessons alone, but because it directly assists the students themselves. Teachers also agreed that the flexibility is a plus point for CEFR-aligned curriculum as it encourages seamless integration of all four skills with communicative competence as the main goal of language exchanges taking place in lessons. However, they were also aware of the fact that appropriation need to be made to ensure meaningful learning take place as some of them voiced concern against the unfamiliar context (culture, received pronunciation, etc.) which may impede the students’ comprehension and ability to accomplish the tasks and develop necessary skills and strategies.